2021
DOI: 10.3390/app11125530
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Current Strategies and Methods for BIM Implementation in the Academic Field

Abstract: Since the international governmental institutions required and/or recommended (according to the regulations of each country and continent) all public works to be certified in the BIM (Building Information Modeling) methodology, public and private institutions and universities have sought to integrate BIM into their production and educational processes. This requires the university academic environment to focus its efforts on training students in this methodology, as they will need to apply it in any future wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…These results show that the BIM methodology provides an exceptional opportunity to carry out a collaborative team project, with coordination and leadership tasks being essential in the professional practice of an engineer. This result is in agreement with other academic BIM proposals [22,[50][51][52][53]. The use of the University-Enterprise environment is only significant in the results of the degree of integration and maturity in teamwork (S 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…These results show that the BIM methodology provides an exceptional opportunity to carry out a collaborative team project, with coordination and leadership tasks being essential in the professional practice of an engineer. This result is in agreement with other academic BIM proposals [22,[50][51][52][53]. The use of the University-Enterprise environment is only significant in the results of the degree of integration and maturity in teamwork (S 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…So Li et al (2019) [4] continued to suggest that the fundamental issue of HBIM is the balance between regularization modeling and differentiation modeling. Therefore, the algorithmic modeling of HBIM could be a better solution because it is easy to repeat with node-visible modeling programs [5][6][7][8][9][10].…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Many studies indicated that BIM can be also used to help students understand the engineering-related knowledge, the design and construction process, the design details, and the related techniques [3,17]. Besides this, the integration of BIM and knowledge ontology will be beneficial for engineering education.…”
Section: Introductionmentioning
confidence: 99%